Immunity Against Coccidiosis in Poultry- A Review - Akhtar, M.; Hafeez, M.A.; Haq, A.U. (International Journal of Poultry Science, 2005)
Coccidiosis is the most important parasitic infection in poultry worldwide. Control is largely limited to good husbandry and prophylactic chemotherapy using a range of drugs against which resistance is rapidly acquired. Attempts at vaccination using conventional vaccines have been disappointing and there is now a need for new approach. These include biology of parasite to identify the life cycle stages that are vulnerable to immune attack; antigenic characterization, heterogenicity; variability; and effector mechanisms responsibility for immunity. The purpose of this review is to update/summarize the recent advances in the development of vaccines against the avian coccidiosis.